WUJUD KESANTUNAN ASERTIF DAN IMPERATIF DALAM BAHASA BANJAR - Rissari Yayuk (Badan Pengembangan dan Pembinaan Bahasa, 2016)
Politeness by the present generation has shifted as a result of various factors. Important to the preservation of a form of politeness that coud be used as a teaching example for increased intelligence-speaking children today and will come in a variety of speech acts. The problem studied include (1) How Being assertive speech act of politeness Banjar, (2) How to form the speech acts imperative Banjar. The aim is to describe, (1) Being assertive speech act of politeness Banjar, and (2) form the speech acts imperative Banjar. This research method is descriptive technique used in data collection and documentation is a recording technique. Sources of data taken from the area which is considered to represent the people of Banjar, namely Banjar. Time data capture for 2 months (of January s.d. End of February 2016). The results showed being politeness contained in an assertive speech act can be seen in the form of pleasantries and politeness sapaan.Wujud words contained in the imperatif speech acts can be seen in the form of pleasantries and greeting words. ABSTRAKKesantunan berbahasa oleh generasi sekarang mengalami pergeseran akibat berbagai faktor. Penting dilakukan pelestarian wujud kesantunan berbahasa yang bsa dijadikan contoh ajar bagi peningkatan kecerdasan berbahasa anak-anak sekarang maupun akan datang dalam ragam tindak tutur. Masalah yang dikaji meliputi (1) Bagaimana Wujud kesantunan tindak tutur asertif dalam bahasa Banjar, dan (2) Bagaimana wujud tindak tutur imperatif dalam bahasa Banjar. Tujuan yang ingin dicapai adalah mendeskripsikan (1) wujud kesantunan tindak tutur asertif dalam bahasa Banjar, dan (2) wujud tindak tutur imperatif dalam bahasa Banjar. Metode penelitian ini adalah deskriptif Teknik yang digunakan dalam pengambilan data adalah teknik rekam dan dokumentasi. Sumber data diambil dari wilayah yang dianggap mewakili masyarakat Banjar, yaitu Kabupaten Banjar. Waktu pengambilan data selama 2 bulan (Januari s.d. Februari 2016). Hasil penelitian menunjukkan wujud kesantunan berbahasa yang terdapat dalam tindak tutur asertif dapat dilihat dalam wujud basa-basi dan kata sapaan. Wujud kesantunan berbahasa yang terdapat dalam tindak tutur imperatif dapat dilihat dalam wujud basa-basi dan kata sapaan.